2003
DOI: 10.1023/a:1024083309982
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Porous nano-hydroxyapatite/collagen/alginate (nHAC/Alginate) composite containing nHAC and Ca-crosslinked alginate is synthesized biomimetically. This composite shows a significant improvement in mechanical properties over nHAC material. Mechanical test results show that the compressive modulus and yield strength of this composite are in direct proportion to the percentage of Ca-crosslinked alginate in the composite. Primary biocompatibility experiments in vitro including fibroblasts and osteoblasts co-culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…The diffraction results of the CSH/nHAC composite prepared in this experiment were same as previously described [37]. CSD appeared owing to the hydration of CSH [24].…”
Section: Resultssupporting
confidence: 61%
“…The diffraction results of the CSH/nHAC composite prepared in this experiment were same as previously described [37]. CSD appeared owing to the hydration of CSH [24].…”
Section: Resultssupporting
confidence: 61%
“…11 Furthermore, it is often used in composite bone graft materials 43–45 because of its excellent biocompatibility and low immunogenicity. 46 Coating scaffolds with SIM-containing alginate resulted in a progressive and sustained release of SIM, as demonstrated for concentrations of 2.4 and 0.6 mM SIM.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CNTs or CNFs embedded in a biodegradable polymer exhibit biocompatibility even after release into blood vessels. The work carried out by Sitharaman et al showed that the in vivo biocompatibility of ultra-short SWCNT/PPF nanocomposites is similar to that of PPF alone, and the tissue response they elicit is similar to that of other polymers and nanocomposites used for tissue engineering [52, 103–106]. Hence, it is anticipated that CNTs or CNFs embedded in biodegradable polymers do not pose a threat to biocompatibility.…”
Section: Discussionmentioning
confidence: 99%